Antitumor activity, cell cycle arrest and apoptosis induction in human colon cancer cell line by Primula macrophylla extracts (Bangladesh Journal of Pharmacology, 2017)
The primary objective of the current work was to investigate the antitumor potential of Primula macrophylla extracts in human colon cancer cell line (Colo-205) along with evaluating the effects on apoptosis induction, cell cycle arrest and mitochondrial membrane potential. Cell viability was assessed by tetrazolium-based MTT assay. Flow cytometry measurement was carried out to assess the effect of the extract on cell cycle phase distribution and mitochondrial transmembrane potential. Results showed that P.  macrophylla methanol extract was effective and exhibited highest cell growth inhibition (IC50 value, 26.17 ?g/mL). Methanol extract significantly increased the side-scattering profile of Colo-205 cells in concentration-dependent pattern. Exposure of Colo-205 cells with different concentrations of the methanol extract (0-80 ?g/mL) caused dose-dependent G0/G1 cell cycle arrest along with inducing apoptotic cascade by increasing the population of cells at G0/G1 phase. Furthermore, methanol extract treatment caused an increase in mitochondrial membrane depolarization in Colo-205 cells.Video Clip of Methodology: 3 min 17 sec   Full Screen  Alternate